KEGIATAN PENGATALOGAN DI PERPUSTAKAAN KELUARGA EFENDI - Asep Saeful Rohman; Evi Nursanti Rukmana; Shanda Efendi (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2022)
In the information era that is growing rapidly and increasingly advanced as it is today, the public's need for information is growing rapidly. Family libraries play an important role in meeting information needs, especially the information needs of library members. Although the scope of the family library is narrow because library members only consist of family members and/or family relatives, but with the existence of a family library, family library members can find their own information needs. Examine how to process library materials in the family library, namely the Efendi Family Library to facilitate users of the Efendi Family Library. This study uses a qualitative descriptive research method. The object of this research is the cataloging system in the Efendi Family Library. This research was conducted from November 15 to December 6, 2021 at the Efendi Family Library. Bibliography regarding the increasing number of user information needs and various user characteristics, the bibliography is used as an effort to improve the quality of information retrieval quickly and accurately. Senayan Library Management system (SLiMS) is a web-based Open Source Software (OSS) to meet the needs of library automation from small to large scale. The utilization of the Senayan Library Management system (SLiMS) application at the Efendi Family Library has not been said to be optimal because it has not utilized the features contained in the Senayan Library Management system (SLiMS) application.